Prevalence of Imposter Syndrome Among Medical Students of Rawalpindi, Islamabad and Lahore: A Cross-Sectional Study Investigating A Trending and Pragmatic Topic: we no Longer Have to Live in Pluralistic Ignorance - Mashhadi, Syed Fawad; Khan, Nazish; Khalid, Rana Abdullah; Raza, Hubab; Hassan, Ateeq Ul; Younas, Muhammad Fahad (Pakistan Armed Forces Medical Journal, 2024)
Objectives: To determine the prevalence of Imposter syndrome among medical students and to assess its association with various sociodemographic factors. Study Design: Analytical cross-sectional study. Replace and During of Study: Public and Private Medical Colleges of Islamabad/Rawalpindi and Lahore Pakistan, from Nov 2021-Apr 2022. Methodology: An analytical cross-sectional study was carried out in Public and Private Medical and Dental Colleges of Islamabad/Rawalpindi and Lahore Pakistan, from Nov 2021 to Apr 2022. Three hundred ninety-nine eligible MBBS/ BDS students were enrolled through non probability convenience sampling. Data was collected Online through a 20 item Clance questionnaire. Data was analysed using SPSS Version-25. Qualitative variables were expressed as frequency and percentages and quantitative variables as mean and S.D. Chi-square test was applied. Results: Out of 399 participants, 254(63.6%) were males and 145(36.3%) were females. Majority of the participants (71.4%) were in age range of 20-22 years. Three hundred and sixty-two (90.7%) participants were students of MBBS, while 37(9.3%)studied in BDS. Two hundred fifty (62.65%) participants suffered from imposter syndrome which showed a positive association with gender (p<0.001), age (p<0.001), year of Study (p<0.001) and academic performance in class (p=0.002). Conclusion: Imposter syndrome is quite prevalent among the high achieving medical students and is associated with various sociodemographic variables. Further in-depth research is needed to confirm its association with mental health issues and its adverse effects on the normal functioning of individuals.